Analyzing Partial Shading in PV Systems Using Wavelet Packet Transform and Empirical Mode Decomposition Techniques - Kais Abdulmawjood; Walid G. Morsi (IEEE Access)
Partial shading in solar photovoltaic (PV) modules typically reduces the output current of the shaded PV module due to the reduction in the irradiance level. Although this phenomenon is temporary in nature, it is considered an intermittent fault, and it is essential for a protection system to differentiate it from other fault conditions to avoid unnecessary tripping. The main problem in identifying partial shading in a PV system is the difficulty of extracting its features under different shading conditions. To solve this difficulty, this article proposes a novel approach combining Wavelet Packet Transform (WPT) along with Empirical Mode Decomposition (EMD) to extract the features of PV panel output voltage and string current signals during partial shading conditions. In the first stage, the WPT is used to split the PV voltage and string currents into specific sub-band frequencies, and then EMD is used to decompose the selected frequency bands into a number of intrinsic mode functions (IMFs) and a residual. The generated IMF components are then fed into the Random Forest (RF) algorithm designed for shading detection and classification. This proposed hybrid technique provides a high-resolution representation of the array voltage and string currents without loss in the time-frequency resolution, aiding in the detection of partial shading and differentiation of its strength. The results indicate that the proposed approach achieved a detection accuracy of 98.43% and a classification accuracy of 97.6%.